PENGEMBANGAN BAHAN AJAR MEMBACA SASTRA BERBASIS KECERDASAN SPIRITUAL BAGI SISWA SD - Prima Vidya Asteria (Universitas Negeri Medan, 2017)
Abstract : The Development Of Teaching For Literature Based On Spiritual Intelegence For SD Students. The general objective of this research is to develop teaching materials of literacy reading based on spiritual intelligence for elementary students. To achieve the objectives, the research used research design adapted from the R2D2 development model. The product of further development is tested to determine the feasibility of the product, namely through three test groups which include (1) expert test, (2) teacher test, (3) student test. The product resulting is teaching materials of literacy reading based on spiritual intelligence for elementary students. Based on the results of this development, it can be seen the feasibility of developed teaching materials. Therefore, it can be concluded that the resulting teaching material is feasible to be implemented in learning literature reading in elementary school. Keywords : Teaching Materials Development, Literacy Reading, Spiritual Intelligence Abstrak : Pengembangan Bahan Ajar Membaca Sastra Berbasis Kecerdasan Spiritual Bagi Siswa SD. Tujuan umum penelitian ini adalah untuk mengembangkan bahan ajar membaca sastra berbasis kecerdasan spiritual bagi siswa SD. Untuk mencapai tujuan penelitian di atas digunakan rancangan penelitian yang diadaptasi dari model pengembangan R2D2. Produk hasil pengembangan selanjutnya diujicobakan untuk mengetahui kelayakan produk, yakni melalui tiga kelompok uji yang meliputi (1) uji ahli (2) uji praktisi (3) uji siswa. Produk yang dihasilkan yaitu bahan ajar membaca sastra berbasis kecerdasan spiritual bagi siswa SD. Berdasarkan hasil pengembangan ini, maka dapat diketahui kelayakan bahan ajar yang dikembangkan. Oleh karena itu, dapat disimpulkan bahwa bahan ajar yang dihasilkan layak diimplementasikan dalam pembelajaran membaca sastra di SD. Kata Kunci : Pengembangan Bahan Ajar, Membaca Sastra, Kecerdasan Spiritual